The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1128/aac.00303-16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Vancomycin in Elderly Patients Aged over 80 Years

Abstract: cSince the 1950s, vancomycin has remained a reference treatment for severe infections caused by Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus. Vancomycin is a nephrotoxic and ototoxic drug mainly eliminated through the kidneys. It has a large interindividual pharmacokinetic variability, which justifies monitoring its plasma concentrations in patients. This is especially important in patients aged over 80 years, who frequently have renal impairment. However, the pharmacokinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…An appropriate PPK model is of importance for achieving vancomycin targeted C ss . Traditionally, vancomycin dosage was determined based on the CLcr estimated by Scr, and most of the vancomycin PPK models were focused on the CLcr . However, many other studies had shown that cystatin C predicted vancomycin trough levels better than Scr in hospitalized patients, and a vancomycin dosing nomogram based on GFR estimated by cystatin C could improve goal trough achievement compared to Scr .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An appropriate PPK model is of importance for achieving vancomycin targeted C ss . Traditionally, vancomycin dosage was determined based on the CLcr estimated by Scr, and most of the vancomycin PPK models were focused on the CLcr . However, many other studies had shown that cystatin C predicted vancomycin trough levels better than Scr in hospitalized patients, and a vancomycin dosing nomogram based on GFR estimated by cystatin C could improve goal trough achievement compared to Scr .…”
Section: Discussionmentioning
confidence: 99%
“…So far, the results of external evaluation reported by 19 vancomycin PPK models concerning adult patients showed that the MPE, MPE%, MAE, MAE% and RMSE ranged from −2.99 to 1.8 mg/l, −7.7% to 17.9%, 0.22 to 9.28 mg/l, 16.4% to 35.1% and 0.45 to 9.19 mg/l, respectively. Almost all these studies took Scr as renal biomarker excepted for the Japanese study .…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients represent a heterogeneous population [50], thus making it difficult to accurately estimate their renal function. Studies have examined several equations in an attempt to elucidate an accurate estimate of renal function: the Cockcroft–Gault (CG) method, the Modification of Diet in Renal Disease (MDRD) method, and the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) method.…”
Section: Key Clinical Issuesmentioning
confidence: 99%
“…Bourguignon and colleagues evaluated the pharmacokinetics of patients over the age of 80 years on vancomycin and found that there can be large inter-individual variability of vancomycin pharmacokinetic parameters. (8) Additional variabilities in protein binding and volume of distribution may also account for the differences in target trough attainment between groups. (23,24) Moreover, the use of serum creatinine as an estimate of renal function in elderly pa-tients may not be reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there remains a sufficient amount of variability in clearance and volume of distribution observed in elderly patients. (8) Elderly patients may also have decreased muscle mass, which can lead to decreases in serum creatinine and affect drug distribution. (9) It has also been described that serum creatinine production in elderly patients may be within normal limits, but renal function may be lower than expected.…”
Section: Introductionmentioning
confidence: 99%